MANAJEMEN SARANA DAN PRASARANA BERBASIS EVALUASI BERKELANJUTAN DALAM MENINGKATKAN KINERJA LAYANAN PEMBELAJARAN DI MTSN 4 SIDOARJO DAN MTSN 2 SURABAYA - Nova Fadliana Rahmawati; Farih Annisa Putri; Sahudi Sahudi (STKIP Pesisir Selatan, 2026)
Educational facilities and infrastructure management plays an important role in improving the quality of learning services in schools. This study aims to analyze the implementation of continuous evaluation-based facilities and infrastructure management in improving the performance of learning services at MTsN 4 Sidoarjo and MTsN 2 Surabaya. The research employed a qualitative approach with a case study design. Data collection techniques were conducted through observation, in-depth interviews, and documentation involving principals, vice principals for facilities and infrastructure, teachers, and educational staff. The results showed that continuous evaluation was implemented in every stage of facilities and infrastructure management, including planning, procurement, utilization, maintenance, and disposal of educational facilities. Evaluation activities were carried out through routine inventories, monitoring facility conditions, and follow-up actions regarding damages and learning needs. The implementation of continuous evaluation had a positive impact on the effectiveness of facility utilization, learning environment comfort, and the improvement of learning service quality in madrasahs. The novelty of this study lies in the integration of continuous evaluation into the entire cycle of facilities and infrastructure management oriented toward improving the quality of learning services systematically and sustainably. This study also emphasizes the importance of participation from all school members in the evaluation process.